2019
DOI: 10.1002/mp.13871
|View full text |Cite
|
Sign up to set email alerts
|

First application of a high‐resolution silicon detector for proton beam Bragg peak detection in a 0.95 T magnetic field

Abstract: PurposeTo report on experimental results of a high spatial resolution silicon‐based detector exposed to therapeutic quality proton beams in a 0.95 T transverse magnetic field. These experimental results are important for the development of accurate and novel dosimetry methods in future potential real‐time MRI‐guided proton therapy systems.MethodsA permanent magnet device was utilized to generate a 0.95 T magnetic field over a 4 × 20 × 15 cm3 volume. Within this volume, a high‐resolution silicon diode array det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Photon dosimetry in magnetic fields has been thoroughly investigated using both,dose measurements and Monte Carlo dose calculations to determine ionization chamber correction factors. [12][13][14][15][16] In comparison, proton dosimetry in magnetic fields is not yet established and it is under active development with investigations employing different complementary techniques, including Monte Carlo simulations, 17 radiochromic films, 18 semi-conductors, 19,20 and ionization chambers. 21 In particular, the findings by Fuchs et al showed that the magnetic field has a small but significant effect on the ionization chamber response (varying from −0.7% to 0.5%).…”
Section: Introductionmentioning
confidence: 99%
“…Photon dosimetry in magnetic fields has been thoroughly investigated using both,dose measurements and Monte Carlo dose calculations to determine ionization chamber correction factors. [12][13][14][15][16] In comparison, proton dosimetry in magnetic fields is not yet established and it is under active development with investigations employing different complementary techniques, including Monte Carlo simulations, 17 radiochromic films, 18 semi-conductors, 19,20 and ionization chambers. 21 In particular, the findings by Fuchs et al showed that the magnetic field has a small but significant effect on the ionization chamber response (varying from −0.7% to 0.5%).…”
Section: Introductionmentioning
confidence: 99%
“…Correction factors have been derived to account for this, and depends on the magnetic field strength and directions 26–31 . For solid state‐based detectors, there is no apparent changes within the bulk of the detection volume, rather the diode packaging and any air‐gaps surrounding the diodes generate changes in the secondary electron fluence 32–35 …”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29][30][31] For solid state-based detectors, there is no apparent changes within the bulk of the detection volume, rather the diode packaging and any air-gaps surrounding the diodes generate changes in the secondary electron fluence. [32][33][34][35] The purpose of the current work is to present the successful workings of a portable device capable of producing strong magnetic fields over a volume large enough to support fundamental small-scale experiments that mimic the environment of an MRI-linac system. The device is given the acronym MARDOS: Magnetic Apparatus for RaDiation Oncology Studies.…”
Section: Introductionmentioning
confidence: 99%
“…The feasibility of integrating MRI-guidance for particle therapy, in terms of dosimetry, treatment planning and imaging, was recently demonstrated [6] , [7] , [8] , [9] .…”
Section: Introductionmentioning
confidence: 99%